Assessment Of Knowledge And Adherence To Medication: A Mixed Methodology Study Among Patients With Type-2 Diabetes Mellitus In Penang - al-Qazaz, Harith Khalid Mohammed (2011)

(untitled)
The prevalence of diabetes mellitus had increased tremendously among the Malaysian population during the last decade. Furthermore, managing diabetes related morbidity is always faced with challenges by the healthcare providers. In order to provide optimal disease management, there is a need for diabetic patients to be exposed to diabetes self management approach. Although numerous measures have been taken to improve glycemic control among patients with diabetes in Malaysia, the results are still unfavorable.